Microelectronics : - Neamen, Donald A. (McGrawHill, 2010)
"Microelectronics: Circuit Analysis and Design" is intended as a core text in electronics for undergraduate electrical and computer engineering students. The fourth edition continues to provide a foundation for analyzing and designing both analog and digital electronic circuits. The goal has always been to make this book very readable and student friendly. An accessible approach to learning through clear writing and practical pedagogy has become the hallmark of "Microelectronics: Circuit Analysis and Design" by Donald Neamen. Now in its fourth edition, the text builds upon its strong pedagogy and tools for student assessment with key updates as well as revisions that allow for flexible coverage of op-amps.